PERANCANGAN APLIKASI SURAT KETERANGAN PENDAMPING IJAZAH (SKPI) BERBASIS WEBSITE - Ariesta Lestari; Felicia Sylviana (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
Department of Informatics Engineering, University of Palangka Raya (UPR) has implemented the KKNI curriculum since 2020. As the output of KKNI Curriculum, student will receive a Surat Keterangan Pendamping Ijazah (SKPI) after they graduated. Currently, there is no system to processes the SKPI in the Department of Informatics UPR. Therefore in this article a design of a system that can handle or help record and print student achievements as stated in the SKPI is introduced. In this article waterfall methodology is used to develop the system. The stages are the analysis, design, coding, testing and maintenance stages. The result of this research is a SKPI information system that can process and print a description of student achievement. In addition, it can also print student activities such as organizational data, competitions, seminars, training, and student courses.